La autonomía y la comunicación en el desarrollo social de los niños de primer año de Educación Básica de la Escuela Fiscomisional Cacha del cantón el Pangui provincia de Zamora Chinchipe año lectivo 2011- 2012. Lineamientos alternativos - Uchuari Paccha, Patricia Yolanda (2013)
Educate is a complex task that requires a great effort, since the ultimate goal is the integral development of our children, to grow in the best conditions, hence in the present investigation entitled " The autonomy and communication in the social development of children of the first year of basic general education of the School of the Cacha Fiscomisional Canton the Pangui, Zamora Chinchipe province. Period 2011 - 2012 ". For this investigation was raised as a general objective, explain the basic influence of autonomy and communication in the Social development of children in the first year of General education of the school "Fiscomisional Cacha" Pangui, province of Zamora Chinchipe in the canton. Period 2011-2012. Methods were employed to this end: scientist during the entire process and research development exploring and defining the subject to be investigated, which helped formulate the objectives and identify possible solutions to the problem, observation, inquiry, on the autonomy and communication in social development, the descriptive methods, helped point out the manifestations of a lack of autonomy and communication It has direct impact on social development, the hypothetico-deductive method served to investigate the hypothesis, and analyze the object of study, draw deductions from the variables and indicators of research, in the same way for the approach of conclusions. The synthetic analytical method served for the interpretive analysis of empirical information and then with the field work and the formulation of conclusions to each variable and indicators. The results from this research indicate that the lack of autonomy and communication affects the social development of children in the first year of basic general education. There are conclusions and give recommendations based on the results obtained, the same to help child workers and parents and for the development of future scientific research.